2014
DOI: 10.1111/jifm.12015
|View full text |Cite
|
Sign up to set email alerts
|

The International Integrated Reporting Framework: Key Issues and Future Research Opportunities

Abstract: This paper has three main aims. First, the paper introduces the concept of integrated reporting () as described by the International Integrated Reporting Council (IIRC). A background to the development of the concept over the 4‐year period from the inception of the IIRC in 2010 is provided, culminating in the release by the IIRC of a Consultation Draft (CD) of the framework in March 2013. Second, the paper discusses key issues currently being debated relating to the CD that the IIRC will need to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
290
0
34

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(334 citation statements)
references
References 29 publications
10
290
0
34
Order By: Relevance
“…Rensburg and Botha (2014) demonstrated that integrated reports were taken as additional disclosures and these reports were taken or used as the main source of information by the very limited number of providers of financial capital. Many studies have addressed the needs of <IR> (Brown and Dillard, 2014;Cheng et al, 2014;Villiers et al, 2014;Adams, 2015). Lee and Yeo (2016) asserted that the benefits of this reporting exceed its costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rensburg and Botha (2014) demonstrated that integrated reports were taken as additional disclosures and these reports were taken or used as the main source of information by the very limited number of providers of financial capital. Many studies have addressed the needs of <IR> (Brown and Dillard, 2014;Cheng et al, 2014;Villiers et al, 2014;Adams, 2015). Lee and Yeo (2016) asserted that the benefits of this reporting exceed its costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The IR proposition builds on the explicit demand for a reporting approach integrating financial and sustainability information suggested by scholars and practitioners on the expectation of improving the decision-making processes for providers of financial capital [71][72][73]. Nevertheless, there is not enough evidence on whether integrated reports are concretely more useful than traditional annual reports in supporting investors' decisions [74][75][76].…”
Section: Disclosing Materials Information: the Hypotheses Developmentmentioning
confidence: 99%
“…Lodhia and Hess confirm that sustainability accounting and reporting practices are evolving but that progress is slow [94]. Cheng et al found that only seven of S&P 500 companies integrated their financial and non-financial information [95]. Dong and Burritt found poor disclosure when examining social and environmental disclosure [96].…”
Section: Discussionmentioning
confidence: 90%